Effect of Serum Interleukin-6 Concentration on the Prognosis After Radiotherapy for Patients With Hepatocellular Carcinoma - Yong Hu; Yongkang Zhou; Shisuo Du; Wenchao Zhu; Yixing Chen; Zhaochong Zeng (Canadian Journal of Gastroenterology and Hepatology)
Conclusions: The prognosis of HCC patients receiving RT was worse for those with a pre-RT serum IL-6 concentration > 7.8 pg/mL than those with a pre-RT serum IL-6 concentration ≤ 7.8 pg/mL. Pre-RT IL-6 concentrations may affect the prognosis of HCC patients.